2015
DOI: 10.1039/c5gc00026b
|View full text |Cite
|
Sign up to set email alerts
|

The effect of steam on the catalytic fast pyrolysis of cellulose

Abstract: The effect of steam for the catalytic fast pyrolysis of cellulose with ZSM-5 was studied in a bubbling fluidized bed reactor. Irreversible and reversible changes due to steaming were identified. Steam caused dealumination, a loss of total acidity, an increase in the zeolite-crystal size, and agglomeration of particles. For runs both with and without steam co-feeding, these irreversible changes caused lower yields for aromatics and char/coke, and higher yields for methane and unidentified products. In addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 50 publications
3
18
1
Order By: Relevance
“…51 Addition of phosphorous to HZSM-5 has been demonstrated to prevent dealumination. Fresh HZSM-5 upgrades biomass pyrolysis vapors to form aromatic hydrocarbons, and when steam is present some oxygenated aromatics are observed (phenol and alkyl phenols, naphthol and alkyl naphthols).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Addition of phosphorous to HZSM-5 has been demonstrated to prevent dealumination. Fresh HZSM-5 upgrades biomass pyrolysis vapors to form aromatic hydrocarbons, and when steam is present some oxygenated aromatics are observed (phenol and alkyl phenols, naphthol and alkyl naphthols).…”
Section: Discussionmentioning
confidence: 99%
“…Silica-supported Ni and V catalysts formed higher amounts of phenols when cofed with steam, with the V catalysts showing increased selectivity towards simple phenols instead of catechols. 51 The fluidizing gas consisted of He and/or steam at various vapor fractions of steam. 49 In an effort to combine the advantages realized from co-feeding steam with metal-based and zeolite catalysts, another study investigated the effect of steam on catalytic upgrading of biomass pyrolysis vapors using metal modified HZSM-5.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al demonstrated that the introduction of steam had irreversible and reversible impacts on the catalyst and product distribution from CFP of cellulose. 40 As shown in Table 3, the steam caused the reduction in yields of aromatics and char/coke and the increase in the yields of methane and CO. The results were partly attributed to the irreversible changes in the morphology and structure of zeolite, including dealumination, a loss of total acidity, an increase in the crystal size of zeolite and agglomeration of particles.…”
Section: Effect Of Moisture On Cfp Of Biomassmentioning
confidence: 96%
“…The moisture in biomass is another important influential factor that should be considered in the CFP. Yang et al demonstrated that the introduction of steam had irreversible and reversible impacts on the catalyst and product distribution from CFP of cellulose . As shown in Table , the steam caused the reduction in yields of aromatics and char/coke and the increase in the yields of methane and CO.…”
Section: Reaction Chemistry For Cfp Of Biomassmentioning
confidence: 99%
See 1 more Smart Citation